2021
DOI: 10.3390/su13116430
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Durability of Cement-Treated Lateritic Soil

Abstract: The transportation infrastructure, including low-volume roads in some regions, needs to be constructed on weak ground, implying the necessity of soil stabilization. Untreated and cement-treated lateritic soil for low-volume road suitability were studied based on Malaysian standards. A series of unconfined compressive strength (UCS) tests was performed for four cement doses (3%, 6%, 9%, 12%) for different curing times. According to Malaysian standards, the study suggested 6% cement and 7 days curing time as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 109 publications
2
21
0
Order By: Relevance
“…that the incorporation of higher hydraulic binders caused a predominant failure plane that induced brittleness. This brittle behavior has been previously reported to be caused by increasing amounts of hydraulic binder [44,45]. Additionally, non-recognizable compressive collapsible failure was noticed in the 5% OPC and 15% SF, 10% OPC and 10% SF, and 15% OPC and 5% SF treated peat, as shown in Figure 8, indicating its structural heterogeneity.…”
Section: Binder's Effect On the Failure Modessupporting
confidence: 64%
See 1 more Smart Citation
“…that the incorporation of higher hydraulic binders caused a predominant failure plane that induced brittleness. This brittle behavior has been previously reported to be caused by increasing amounts of hydraulic binder [44,45]. Additionally, non-recognizable compressive collapsible failure was noticed in the 5% OPC and 15% SF, 10% OPC and 10% SF, and 15% OPC and 5% SF treated peat, as shown in Figure 8, indicating its structural heterogeneity.…”
Section: Binder's Effect On the Failure Modessupporting
confidence: 64%
“…However, it was observed that the utilization of hydraulic binders increased stiffness and thus led to a change in the failure mode. This type of failure mode is associated with ductile behavior [ 44 ]. The bulging failure mode subsided, and a compressive V-shaped failure pattern was observed in the 10% SF and 15% OPC treated UCS samples, which indicated a reduction in the ductility with the use of a hydraulic binder.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of cement will react with water to produce cement hydrate [ 40 ] that forms a cement-soil skeleton between soil particles [ 29 ], which makes the soil particles more closely connected and increases the friction resistance on the surface of the particles. With the increase in cement content, cement hydrate even generates gel to wrap soil particles to form aggregates ( Figure 13 a,c), which makes the soil cemented and hardened.…”
Section: Discussionmentioning
confidence: 99%
“…Red soil, which indicates all laterite soils is a highly weathered soil under heavy rains containing secondary oxides of iron, aluminium and manganese [13]. Given the silica-alumina ratio (𝑆𝑖𝑂 2 /𝐴𝑙 2 𝑂 3 ), the laterites are classified into three groups [14]. The true laterites have a ratio of less than 1.33, the soil with a ratio between 1.33 and 2 is lateritic, and finally, the ratio greater than 2 indicates non-lateritic tropically weathered soils.…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that the base swelling had been occurred due to soil-atmosphere interaction. Thus, stabilisers like cement have been employed to improve the characteristics of the lateritic soil [14]. Depending on pedogenic and genesis, the index and geotechnical properties of lateritic soil vary to a vast extent [25][26][27].…”
Section: Introductionmentioning
confidence: 99%